2016
DOI: 10.1165/rcmb.2015-0373oc
|View full text |Cite
|
Sign up to set email alerts
|

Phosphodiesterase 4 Inhibitors Attenuate the Asthma Phenotype Produced by β2-Adrenoceptor Agonists in Phenylethanolamine N-Methyltransferase–Knockout Mice

Abstract: Mice lacking the endogenous b 2 -adrenoceptor (b 2 AR) agonist epinephrine (phenylethanolamine N-methyltransferase [PNMT]-knockout mice) are resistant to developing an "asthma-like" phenotype in an ovalbumin sensitization and challenge (Ova S/C) model, and chronic administration of b 2 AR agonists to PNMT-KO mice restores the phenotype. Based on these and other studies showing differential effects of various b 2 AR ligands on the asthma phenotype, we have speculated that the permissive effect of endogenous epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 48 publications
0
23
0
Order By: Relevance
“…While PAR 2 Ϫ/Ϫ mouse models have been used to evaluate the role for house dust mite- (15) or cockroach-induced asthma (16,45), examination of ␤-arrestin-2 signaling arm for PAR 2 activation has provided further clues in understanding the mechanisms that underlie allergic asthma. That GPCR/␤-arrestin signaling pathways are important mediators of inflamma-tion, and airway hyperresponsiveness is corroborated by other studies in ovalbumin-induced and cigarette smoke-induced allergic asthma animal models (11,68) and by studies showing that some of the adverse effects associated with ␤ 2 -adrenergic receptor activation are ␤-arrestin dependent (20,64). Our studies suggested that PAR 2 -stimulated, ␤-arrestin-dependent cell migration is a major contributing factor to the cellular inflammation observed during asthma.…”
Section: Discussionmentioning
confidence: 58%
“…While PAR 2 Ϫ/Ϫ mouse models have been used to evaluate the role for house dust mite- (15) or cockroach-induced asthma (16,45), examination of ␤-arrestin-2 signaling arm for PAR 2 activation has provided further clues in understanding the mechanisms that underlie allergic asthma. That GPCR/␤-arrestin signaling pathways are important mediators of inflamma-tion, and airway hyperresponsiveness is corroborated by other studies in ovalbumin-induced and cigarette smoke-induced allergic asthma animal models (11,68) and by studies showing that some of the adverse effects associated with ␤ 2 -adrenergic receptor activation are ␤-arrestin dependent (20,64). Our studies suggested that PAR 2 -stimulated, ␤-arrestin-dependent cell migration is a major contributing factor to the cellular inflammation observed during asthma.…”
Section: Discussionmentioning
confidence: 58%
“…Eosinophils were determined as a percentage of the total cells in each field and expressed as percent eosinophil. 23, 47 …”
Section: Methodsmentioning
confidence: 99%
“…If confirmed, this highlights the need to understand the structural elements in these ligands that preferentially stabilize the β 2 ‐adrenoceptor in this unwanted conformation. One means to compensate for adverse‐effects mediated by β‐arrestin‐dependent ERK activation is to offset bias by enhancing LABA‐induced, cAMP signalling with a PDE4 inhibitor (Forkuo et al , ; Pera and Penn, ). Indeed, in sensitized and challenged PNMT ‐deficient mice, roflumilast and rolipram prevented formoterol and salmeterol from restoring the asthma‐like phenotype when compared with wild‐type animals.…”
Section: Optimizing Ics/laba Combination Therapy By Exploiting Pharmamentioning
confidence: 99%
“…This effect may not only protect against MAPK‐dependent desensitization (Nino et al , ) but should also reduce unwanted signalling due to biased agonism from the β 2 ‐adrenoceptor. Thus, reducing the effect of β 2 ‐adrenoceptor‐mediated, β‐arrestin signalling with a PDE4 inhibitor and/or a glucocorticoid could tip the balance away from ‘pro‐asthma’ effects towards more favourable ‘therapeutic’ outcomes (Forkuo et al , ; Pera and Penn, ).…”
Section: Optimizing Ics/laba Combination Therapy By Exploiting Pharmamentioning
confidence: 99%